Multi-analyte profiling of inflammatory mediators in COPD sputum – The effects of processing. Issue 2 (February 2015) - Pedersen, Frauke; Holz, Olaf; Lauer, Gereon; Quintini, Gianluca; Kiwull-Schöne, Heidrun; Kirsten, Anne-Marie; Magnussen, Helgo; Rabe, Klaus F.; Goldmann, Torsten; Watz, Henrik
Highlights The Luminex-based xMAP® panel can be used for multi-analyte profiling of COPD sputum. No adaptation in standardized sputum processing required. Dithiothreitol can be used but potentially affects absolute mediator concentrations.